A Distinctive Spinach‐Based Carbon Nanomaterial with Chlorophyll‐Rich and Near‐Infrared Emission for Simultaneous In Vivo Biothiol Imaging and Dual‐Enhanced Photodynamic Therapy of Tumor. Issue 7 (10th April 2019) - Liu, Rongjun; Zhang, Liangliang; Zhao, Jingjin; Hou, Cheng; Huang, Yong; Huang, Zirong; Zhao, Shulin
Abstract: Photodynamic therapy (PDT) is a new treatment modality against local lesions, particularly in malignant tumors. However, higher biothiol concentrations in tumor cells will decrease the efficacy of PDT. To tackle the above challenges, a distinctive spinach‐based carbon nanomaterial called "chlorophyll‐rich biomass quantum dots" (CBQDs) with near‐infrared emission is prepared, and the CBQDs are further bound with copper ions forming CBQD‐Cu nanocomposites, which are used as a new fluorescence nanoprobe and highly efficient photosensitizer for simultaneous in vivo near‐infrared fluorescence imaging of biothiol and dual‐enhanced PDT of tumors. The mechanism of action is studied and it is shown that the binding of chlorophyll and copper ions on the surface of CBQDs reduces the energy level difference of the chlorophyll molecules, which results in an increase of reactive oxygen species (ROS) achieving enhanced PDT. On the other hand, the copper ions on the CBQD‐Cu surface can also bind with biothiol which decreases the concentration of free biothiol in tumor cells, and further enhances PDT. At the same time, the combination of copper ions and biothiol opens the fluorescence of CBQDs, which realizes near‐infrared fluorescence imaging of biothiol. Hence, the CBQD‐Cu is used as a highly effective nanomedicine for the recognition and treatment of tumors. Abstract : A novel spinach‐based multifunctional carbon nanomaterial, called "chlorophyll‐rich biomass quantum dots" (CBQDs) with near‐infrared emission is prepared, and the CBQDs are further bound with copper ions forming CBQD‐Cu nanocomposites, which are used as new fluorescence nanoprobes and highly efficient photosensitizers for in vivo near‐infrared fluorescence imaging of biothiol and dual‐enhanced photodynamic therapy of tumors.